Determination of ZAP70 expression as a prognostic marker of chronic lymphocytic leukemia - Vygovska, Olga; Pelenyo, Nataliya; Dzis, Ivan; Horodyska, Tetiana; Boyko, Olha; Schevchenko, Larysa (ScienceRise: Medical Science, 2019)
Chronic lymphocytic leukemia (CLL) is a clinically and biologically heterogeneous disease. Some patients live for decades without any therapy, others die several years after diagnosis, despite the use of different lines of therapy. Significant progress has been achieved in the study of the pathogenesis of CLL, but over the past two decades there has been an intensive search for new biomarkers that may include a prognosis and also decide on therapeutic tactics. In conditions where complex genetic studies are expensive and inaccessible for routine analysis, the determination of ZAP70 remains relevant and sufficiently accessible to predict the course of CLL. Aim of the research: to evaluate the prognostic significance of the level of expression of ZAP70 and its dependence on the stage of the disease in patients with chronic lymphocytic leukemia. Materials and methods: under our supervision, there were 68 patients with chronic lymphocytic leukemia at various stages of the disease, among them 24 women aged 40-84 years (median 65 years) and 44 men aged 43-84 years (median 63 years). 51 patients received adequate treatment. Immunophenotypic studies of the lymphoid cell population and ZAP70 were performed using flow cytometry. Results of the research: indicators of expression of ZAP70 in patients at different stages of the disease did not differ significantly. Overall survival in the group of patients with ZAP70 expression <20% was significantly higher compared with patients with ZAP70 expression >20%. Conclusions: in CLL patients, the level of expression of ZAP70 is stable, does not depend on the stage of the disease, and does not change during the progression of the disease. ZAP70 expression level >20% of cells is a poor prognostic marker of the course of the disease and indicates a high risk of the disease.